Thylakoid system disassebbly during bleaching of aurea mutants of maple Acer negundo hassk. var. Odessanum - Fulgosi, Hrvoje (Array, 2008)
Summary: Biogenesis of chloroplast photosynthetic membranes is a still not very well understood series of molecular events. Apart from performing photosynthesis reactions, these specialized biomembranes possess the ability of rearrangement to adapt to the ever-changing light environment. In this work, urea mutants of wild-growing maple trees were used to study events that lead to damage and disassembly of thylakoid membranes during the vegetation season. Plastid ultrastructural changes, changes in the composition of photosynthetic pigments and proteins, as well as the efficiency of photosystem II were monitored. It was concluded that strong photoinhibitory processes, coupled with the degradation of proteins, are responsible for the relatively fast reduction of photosynthetic membranes in aurea-type chloroplasts. It is evident that lipid constituents of thylakoid membranes are less susceptible to degradation processes. Once severely damaged, photosynthetic membranes of aurea-type leaves are no longer able to reconstitute the intertwined and functionally intact internal membrane system